2017
DOI: 10.1177/0034355217723553
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Rehabilitation Counseling of Adults With Physical Disabilities: Views of Practitioners Across Countries

Abstract: The purpose of the study is to understand the views of practitioners across countries, on spirituality for rehabilitation counseling of adults with congenital and acquired disabilities. A survey of 1,269 practitioners in the field of disability across 15 countries was conducted. Results showed that practitioners had a favorable view of spirituality. Logistic regression results highlight several crosscountry nuances in practitioners' views toward spirituality for rehabilitation counseling, and more so, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, Ray (2004) said that spirituality should be considered as a coping mechanism, too. Pandya (2019) conducted research on stating rehabilitation counselor's perspectives about spirituality. It included 1,269 practitioners from 15 countries, and the results showed that great numbers of practitioners across countries tend to use a spiritual approach in their cases.…”
Section: Spirituality In Rehabilitation Psychologymentioning
confidence: 99%
“…However, Ray (2004) said that spirituality should be considered as a coping mechanism, too. Pandya (2019) conducted research on stating rehabilitation counselor's perspectives about spirituality. It included 1,269 practitioners from 15 countries, and the results showed that great numbers of practitioners across countries tend to use a spiritual approach in their cases.…”
Section: Spirituality In Rehabilitation Psychologymentioning
confidence: 99%